Development of the Nursing Service System for End-Stage Renal Disease Received Hemodialysis by One Stop Service Method in Mahasarakham Hospital - Duangmartpol, Kachanakan; Taiwong, Anucha; Sreesarn, Pimvalanch; Laoburee, Piyapat; Sreyowong, Pikun; Dana, Kamthorn (Princess of Naradhiwas University Journal, 2025)
This research and development aimed to develop and evaluate a one-stop nursing service system for end-stage renal disease patients receiving hemodialysis. The study consisted of 4 phases: 1) situation and problem analysis, 2) nursing service system development, quality verification, and pilot study, 3) effectiveness evaluation using a quasi-experimental research design with two groups comparing pre-test and post-test results, and 4) evaluation, modification, and quality confirmation of the system. Research instruments included focus group discussion guidelines, patient data recording forms, professional nursing practice recording forms, knowledge assessment tools, nursing practice capability assessment forms, patient satisfaction assessment forms, and nurse satisfaction assessment forms. All instruments were validated by three experts. The research was conducted between February - December 2024. Data were analyzed using descriptive statistics and content analysis. The results revealed that the developed nursing service system was consistent with the patient care context and practitioner needs. It comprised three components: structure, process, and outcome, referred to as the C-K-D model, covering four phases of care. After implementing the developed system, findings showed reduced service steps and waiting times, with patients receiving faster and more convenient services. Professional nurses demonstrated increased knowledge and competency. Both patients and professional nurses reported the highest level of satisfaction. Furthermore, quality of care indicators showed improving trends and met target criteria, indicating that the developed nursing service system could enhance care quality efficiently and effectively. However, continuous monitoring is recommended.